Pengaruh Faktor Keputusan Penggunaan Layanan Linkaja Syariah di Masa Covid-19 Dengan Efektivitas Sebagai Variabel Moderasi - Ananda Annisa putri; Fitri Yetti (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
The LinkAja Syariah service is one of the sharia digital payments fintechs in Indonesia and its features can support activities during the pandemic. However, the use of LinkAja Syariah is still not popular because Islamic economic literacy is still low. Therefore, it is necessary to investigate the factors that cause the decision to use these services. The purpose of this study is to explain the effect of promotion, convenience, and service features and there is a moderation of effectiveness on decisions to use LinkAja Syariah services. The approach used in this research is quantitative based on primary data. The sample is 200 users of LinkAja Syariah services in Jabodetabek using purposive sampling method. The data analysis technique used with SmartPLS is path analysis and data collection is obtained by questionnaire. The results of this study are the promotion of a negative and significant influence, the ease of a positive and significant influence, and service features a positive and significant influence on the decision to use. Moderation of effectiveness weakens the relationship between promotions and service features with usage decisions, and effectiveness can strengthen the relationship between convenience and use decisions. This research is expected to provide input to LinkAja Syariah services for product service development.